2015
DOI: 10.1016/j.jccw.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a No-sting Barrier Film Treatment Protocol Compared to Routine Clinical Care for the Treatment of Stage 1 and 2 Pressure Injuries in Long-term Care

Abstract: Pressure injuries increase morbidity and mortality in geriatric patients by 400%. Residents in long-term care (LTC) are at high risk of developing pressure injuries because of limited mobility, poor nutritional status, impaired cognition, and incontinence. This study aims to determine whether a no-sting barrier film (NSBF) treatment protocol is more effective than current physician practices for treating stage 1 and 2 pressure injuries in LTC. A retrospective cohort study of 129 residents from one LTC facility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The film layer was applied once per day after milking on Monday, Wednesday, and Friday or on Tuesday, Thursday, and Saturday. The coating or film protects the skin from contamination and irritation by dirt in the environment (feces, urine, bedding, and so on) and reduces friction (Cameron et al, 2005;Holroyd and Graham, 2014;Chan and Siu, 2016).…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The film layer was applied once per day after milking on Monday, Wednesday, and Friday or on Tuesday, Thursday, and Saturday. The coating or film protects the skin from contamination and irritation by dirt in the environment (feces, urine, bedding, and so on) and reduces friction (Cameron et al, 2005;Holroyd and Graham, 2014;Chan and Siu, 2016).…”
Section: Study Protocolmentioning
confidence: 99%
“…Therefore, the aim of our study was to perform a randomized clinical trial to assess the clinical effectiveness of 2 different topical treatments, one for mild and one for severe UCD lesions, compared with untreated control groups. None of treatments contained antibiotics and the choice of treatments was based on evidencebased research in human medicine (Cameron et al, 2005;Beele et al, 2012;Chan and Siu, 2016). The topical treatment for mild UCD lesions consisted of a nonalcoholic film layer and focused on the protection of the lesion from moisture and dirt.…”
Section: Introductionmentioning
confidence: 99%
“…1 One observational study reported that the application of a commercial no-sting barrier film was associated with reductions in the healing time of stage I and II pressure injuries in patients receiving long-term care. 6 The authors note, however, that the treatment protocol included informal educational and mentoring components, thus making it difficult to differentiate the preventive effect of the skin barrier film from that of the other intervention components. Given that the data regarding the effectiveness of skin barrier films are unclear, we decided to conduct a project to determine the effectiveness of a skin barrier film in preventing skin blisters in surgical patients at our institution.…”
mentioning
confidence: 99%
“…Previous research generally supports using a silicone or liquid skin barrier film as a protective interface between the skin and an adhesive dressing to reduce the risk of skin blistering . One observational study reported that the application of a commercial no‐sting barrier film was associated with reductions in the healing time of stage I and II pressure injuries in patients receiving long‐term care . The authors note, however, that the treatment protocol included informal educational and mentoring components, thus making it difficult to differentiate the preventive effect of the skin barrier film from that of the other intervention components.…”
mentioning
confidence: 99%